Effect of Glycemia on Early Prognosis of Patients with a History of Myocardial Infarction without 2 Type Diabetes (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Goal. To determine the effect of glycemic levels recorded during hospitalization for myocardial infarction (MI) on the early prognosis of patients without previously diagnosedдиа- бетаtype 2 diabetes 2 mellitus (DM - 2).Material and methods. A prospective examination of 296 patients was performed. Three groups were formed according to the level of glycemia at admission: I - 4.0 mmol/ l (7.4%); II-4.01–7.79 mmol/l (69.9%); III — 7.8 mmol/l (22.6%). The частота incidenceе- of нарушений carbohydrate metabolism disorders and развития MI complications ИМ in the hospital period was studied.Results. In 2/3 of patients with glycemia 7.8 mmol/l at поступле- нииadmission, later according to the standard glucose tolerance test (CTG) выявлены нарушения , carbohydrate metabolism disorders were detected: prediabetes (36.9%) and СД-2 type 2 diabetes (32.3%). У Patients III in group III were more likely to have three- fold поражение coronary artery disease (41.8%) and MI complications : congestive left ventricular failure-52.2% vs 27.3% in group I and 34.1% in II group II (p=0.017), cardiogenic shock - 26.9% vs 4.5% and 6.8% (p